Using a computational cognitive model to simulate the effects of personal and social network experiences on seasonal influenza vaccination decisions - Walsh, Matthew M.; Parker, Andrew M.; Vardavas, Raffaele; Nowak, Sarah A.; Kennedy, David P.; Gidengil, Courtney A. (Frontiers in Epidemiology, 2024)
The substantial societal costs of seasonal influenza include illness, loss of lives, and loss of work productivity. Vaccination is the most effective means for averting the disease, yet fewer than half of adults in the United States are vaccinated annually. In this research, we focus on how personal experience and the experiences of close social contacts contribute to vaccination decisions. The results of a multi-year longitudinal survey study revealed the significant effects of personal and social network experiences on vaccination. We develop a memory-based model of vaccination decisions using the Adaptive Control of Thought -Rational (ACT-R) integrated cognitive architecture. The model accounts for the effects of personal and social experience on vaccination and suggests interventions that may be effective in increasing vaccination uptake.